1998
DOI: 10.1021/jf980536s
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Volatile Compounds from the Reaction of 3-Hydroxy-2-butanone and Ammonium Sulfide Model System

Abstract: The reactions between 3-hydroxy-2-butanone and ammoniun sulfide at 25, 50, 75, 100, 125, and 150 degrees C were studied. Four well-known flavor compounds, 2,4,5-trimethyloxazole, 2,4, 5-trimethyl-3-oxazoline, 2,4,5-trimethylthiazole, and 2,4, 5-trimethyl-3-thiazoline, were identified. Another four interesting intermediate compounds, 2-(1-hydroxyethyl)-2,4, 5-trimethyl-3-oxazoline, 2-(1-mercaptoethyl)-2,4, 5-trimethyl-3-oxazoline, 2-(1-hydroxyethyl)-2,4, 5-trimethyl-3-thiazoline, and 2-(1-mercaptoethyl)-2,4, 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The I‐F group contained higher acetoin levels than those of all other groups ( p < .001), likely because lactic acid bacteria in starter cultures can produce acetoin via pyruvate metabolism (Montanari et al, 2016). Acetoin can form at low temperatures (e.g., 80°C) and react with ammonia to form heterocyclic aroma compounds (Liu, Liu, He, Song, & Chen, 2015; Xi, Huang, & Ho, 1998). Levels of 2,3‐octanedione were highest in the N‐F group ( p < .001) due to pyruvate metabolism in the starter culture (Montanari et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The I‐F group contained higher acetoin levels than those of all other groups ( p < .001), likely because lactic acid bacteria in starter cultures can produce acetoin via pyruvate metabolism (Montanari et al, 2016). Acetoin can form at low temperatures (e.g., 80°C) and react with ammonia to form heterocyclic aroma compounds (Liu, Liu, He, Song, & Chen, 2015; Xi, Huang, & Ho, 1998). Levels of 2,3‐octanedione were highest in the N‐F group ( p < .001) due to pyruvate metabolism in the starter culture (Montanari et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…10 If sulfide is present in acetoin/ammonium reaction systems, similar sulfur-containing heterocyclic compounds will be produced. 80 HE-TM-oxazoline was manifested to be relatively unstable, and TTMP would be the main product either under an elevated reaction temperature 79 or in a prolonged storage time. 78 The dynamics of TTMP and its precursors during the industrial production process of a Chinese vinegar were investigated using GC-MS. 73 The results indicated that the main precursor of TTMP, that is, acetoin, was accumulated in the fermentation process, and then it condensed to TTMP during the subsequent storage period.…”
Section: ■ Interconversions and Derivativesmentioning
confidence: 99%
“…Le Quéré et al also hypothesized a chemical synthesis route of 2-alkyl-2,4,5-trimethyl-2,5-dihydrooxazole homologues in cheese from the precursors including acetoin, ammonia, and methyl ketones, which are abundant in cheeses . If sulfide is present in acetoin/ammonium reaction systems, similar sulfur-containing heterocyclic compounds will be produced …”
Section: Interconversions and Derivativesmentioning
confidence: 99%
“…For example, the formation pathway of oxazolines and thiazolines was revealed via model reaction of 3-hydroxy-2-butanone and ammonium sulfide. 3 Schieberle used the Carbon Module Labeling (CAMOLA) technique in model systems to identify transient intermediates in the formation of Maillard flavor products. 4 Overall, Maillard model reactions offer a significant way to achieve varieties of flavor compounds and specific desired flavors.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, specific flavor compounds or intermediates derived from Maillard reaction could also be involved in the model system. For example, the formation pathway of oxazolines and thiazolines was revealed via model reaction of 3-hydroxy-2-butanone and ammonium sulfide . Schieberle used the Carbon Module Labeling (CAMOLA) technique in model systems to identify transient intermediates in the formation of Maillard flavor products .…”
Section: Introductionmentioning
confidence: 99%